The The Relationship between Completeness of Medical Information and Accuracy of Diabetes Mellitus Diagnosis Codes in Inpatient Medical Record Documents in RSUD Ajibarang: The Relationship between Completeness of Medical Information and Accuracy of Diabetes Mellitus Diagnosis Codes in Inpatient Medical Record Documents in RSUD Ajibarang - Nur Istiqomah, Rosita; Sri Wariyanti, Astri; Asmo Sutrisno, Trismianto (Indonesian Journal of Health Information Management, 2025)
Completeness of medical information is very important in supporting the accuracy of diabetes mellitus diagnosis codes. This study aims to determine the relationship between completeness of medical information and the accuracy of Diabetes Mellitus diagnosis codes in inpatient medical record document. This research uses analytical observasional with a cross sectional approach. The sample used was 105 document using a simple random sampling technique. Data analysis used the Chi-Square test. The percentage of complete medical information was 81%, while incomplete was 19%. The highest incompleteness in diagnosis was 13 documents (12%). The percentage accuracy of the diagnosis code is 50%, while the percentage of accuracy is 50%. The most inaccuracies were due to not using dagger and asterisk codes in 18 documents (35%). The Chi-Square statistical test shows that p=0,042. The conclusion is that there is a relationship between the completeness of medical information and the accuracy of diabetes mellitus diagnosis codes. The author suggests that doctors and PPA should immediately complete incomplete medical record documents, especially important sheets relating to the classification and coding of diseases to support accurate coding, and koders should not only refer to ICD 10 volume 3, but must also refer to ICD volume 1 and volume 2.